Comparative Effectiveness of FOLFIRINOX Versus Gemcitabine and Nab-paclitaxel in Initially Unresectable Locally Advanced Pancreatic Cancer: A Population-based Study to Assess Subsequent Surgical Resection and Overall Survival. Issue 5 (May 2023) - Dai, W.F.; Habbous, S.; Saluja, R.; Beca, J.M.; Raphael, M.; Arias, J.; Gavura, S.; Earle, C.C.; Biagi, J.J.; Coburn, N.; Chan, K.K.W.
Abstract: Aims: First-line FOLFIRINOX (FOLinic acid, Fluorouracil, IRINotecan, and OXaliplatin) and gemcitabine plus nab-paclitaxel (GnP) have been publicly funded for patients with unresectable locally advanced pancreatic cancer (uLAPC) in Ontario, Canada. We examined the overall survival and surgical resection rate after first-line FOLFIRINOX or GnP and determined the association between resection and overall survival in patients with uLAPC. Materials and methods: We conducted a retrospective population-based study including patients with uLAPC who received first-line treatment FOLFIRINOX or GnP from April 2015 to March 2019. The cohort was linked to administrative databases to ascertain demographic and clinical characteristics. Propensity score methods were used to balance differences between FOLFIRINOX and GnP. The Kaplan–Meier method was used to calculate overall survival. Cox regression was used to determine the association between receipt of treatment and overall survival, adjusting for time-dependent surgical resections. Results: We identified 723 patients with uLAPC (mean age = 65.8, 43.5% female) who received FOLFIRINOX (55.2%) or GnP (44.8%). The median overall survival and 1-year overall survival probability were higher for FOLFIRINOX (13.7 months, 54.6%) than for GnP (8.7 months, 34.0%). Post-chemotherapy surgical resection occurred in 89 (12.3%) patients (FOLFIRINOX: 74 [18.5%] versus GnP: 15 [4.6%]), with no difference in survival since surgery between FOLFIRINOX and GnP ( P = 0.29). After adjusting time-dependent post-treatment surgical resection, FOLFIRINOX (inverse probability treatment weighting hazard ratio 0.72, 95% confidence interval 0.61, 0.84) was independently associated with improved overall survival. Conclusions: In this real-world population-based study of patients with uLAPC, FOLFIRINOX was associated with improved survival and higher resection rates. FOLFIRINOX was associated with improved survival in patients with uLAPC after accounting for the effect of post-chemotherapy surgical resection, suggesting the benefit of FOLFIRINOX was not solely due to improving resectability. Highlights: In the real world, FOLFIRINOX is associated with improved overall survival and higher post-chemotherapy surgical resection rates in uLAPC patients. ULAPC patients who received subsequent resection after first-line treatment had improved overall survival. Survival benefit of FOLFIRINOX remains after adjusting for resection, suggest its benefit is not solely due to improving resectability of uLAPC.